2021
DOI: 10.7759/cureus.18574
|View full text |Cite
|
Sign up to set email alerts
|

Acute Limb Ischemia in a Patient With COVID-19 Pneumonia

Abstract: COVID-19, which is caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2), is known to cause a myriad of complications along with the typical lower respiratory tract involvement. One of the emerging complications is a hypercoagulable state leading to venous or arterial thromboembolism. These complications are more common in those presenting with a severe disease with significantly elevated inflammatory markers. Although co-morbid illnesses play a role in worsening such complications, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Similar case was reported in Pakistan, Lahore, where an elderly patient with comorbidities presented with fever and lower leg discoloration in which became a non-salvageable limb and required subsequent amputation of the affected limb [ 2 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Similar case was reported in Pakistan, Lahore, where an elderly patient with comorbidities presented with fever and lower leg discoloration in which became a non-salvageable limb and required subsequent amputation of the affected limb [ 2 ].…”
Section: Discussionsupporting
confidence: 66%
“…Although respiratory symptoms predominate in patients with COVID-19, thrombosis can also occur. There have been reports of ALI observed mostly among adults with comorbidities [ 2 5 , 7 ] and only one case has been reported in an adolescent [ 6 ], but to our knowledge, no cases at the time of writing of this case has been reported in younger age groups. This is the first reported case of a four-year-old with ALI due to COVID-19.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…1 An acute limb ischemia may present in the form of chilblains, bullae, acral cyanosis, bruising, blood blisters, acute limb ischemia and lifethreatening gangrene. [4][5][6] Shao et al reported that an acute upper limb ischemia may be the first manifestation of COVID-19 infection. 7 In a review of 27 studies including 5 cohorts, 5 case series, and 17 case reports, Cheruiyot et al found that arterial thrombosis had occurred in about 4% of critically ill COVID-19 patients which could affect multiple arteries.…”
Section: Iranian Medicinementioning
confidence: 99%